Impulse buying on marketplace applications: shopping patterns of Tiktok Shop consumers TiktokShop - Aghnia Salma Salsabila; Moechammad Nasir; Kussudyarsana Kussudyarsana (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of Fear of Missing Out (FOMO) and storytelling marketing on purchase decision in the TikTokShop platform, with impulse buying as a mediating variable. A quantitative approach was employed by distributing questionnaires to 300 respondents in the Madiun Residency areaespecially Ponorogo Regency and Pacitan Regency , selected through purposive sampling. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results reveal that FOMO and storytelling marketing have a significant positive effect on impulse buying, which subsequently mediates consumer purchase decisions. These findings strengthen previous literature emphasizing the role of psychological factors and narrative-based marketing strategies in driving consumer behavior within the digital commerce era. From a practical perspective, this study provides implications for businesses to optimize digital marketing strategies by leveraging psychological urgency (FOMO) and persuasive narratives to enhance promotional effectiveness and foster customer loyalty in social media-based e-commerce ecosystems.